Dynamics of the sealing zone in cultured osteoclasts. Issue 2 (8th February 2017) - Batsir, Sarit; Geiger, Benjamin; Kam, Zvi
Abstract: Bone resorption by osteoclasts (OCs) depends on the formation and stability of the sealing zone (SZ), a peripheral belt of actin and integrin‐based podosomes. Recent studies demonstrated that the SZ is a highly dynamic structure, undergoing cycles of assembly and disassembly. In this study, we explored the mechanisms underlying the regulation of SZ stability and reorganization in OCs cultured on glass slides, and forming an SZ‐like podosome belt (SZL). By monitoring this belt in cultured RAW264.7 cells expressing GFP‐tagged actin, we show here that SZL stability is usually locally regulated, and its dissociation, occurring mostly in concave segments, is manifested in the loss of both podosome coherence, and actin belt continuity. Double labeling of cells for actin and tubulin indicated that microtubules (MTs) are mostly confined by the inner aspect of the stable SZL‐associated actin belt. However, in unstable regions of the SZL, MTs tend to extend radially, across the SZL, toward the cell edge. Disruption of MTs by nocodazole induces SZ disassembly, without affecting individual podosome stability. Inspection of the MT network indicates that it is enriched along stable SZL regions, while bypassing disorganized regions. These results suggest that the SZL is stabilized by MTs flanking its inner aspect, while disruption or misalignment of MTs leads to SZL destabilization. We further demonstrate that the MT‐associated protein dynamin2 is involved in the regulation of SZL stability, and dynamin2 knockdown or inactivation cause SZL destabilization.